Impact of oak wood modalities on the (non)-volatile composition and sensory attributes of red wines - María Reyes González-Centeno; Pierre-Louis Teissedre; Kleopatra Chira (OENO One, 2021)
During fermentation or ageing of wines, oak wood is commonly used in form of barrels, casks or derived oak products (chips, winewoods, tankstaves, among others). It is well known that aroma, structure, astringency, bitterness, aromatic persistence and colour may change as a result of wine‒wood contact. A full-scale experimentation was performed under different oak ageing conditions in order to evaluate colour, phenolic, aromatic and sensory differences among final red wines (9‒months ageing). Oenological parameters and wine colour were not impacted by ageing modality. At the end of ageing, no differences were found in total phenolic and tannin contents. Regardless of the ageing modality, total content and profile of fruity volatiles were globally maintained with regard to control (≥ 86 %). In contrast, the higher the surface of wine‒wood contact per unit of wine volume, the greater the extraction of woody aromas. Thus, barrels led to wines with the highest level of woody aromas (515‒864 µg/L), followed by cask modalities (430‒470 µg/L). From a sensory point of view, descriptors highlighting the woody character of wine (vanilla, spicy) were enhanced in all oak‒aged wines when compared to control. However, our results indicate that a masking effect of fruity aroma by oak wood did not occur, since all modalities were perceived as fruity as the control. Thus, each oak ageing modality may lead to wines with a different woody character, without no impact on fruity perception, allowing wineries to achieve the targeted aromatic profile, good structure and just the right balance between fruity and woody aromas.